Guaranteed crowdlending loans: A tool for entrepreneurial finance ecosystem sustainability - Carlos Sanchís-Pedregosa; Emma Berenguer; Gema Albort-Morant; Jorge Antón Sanz (Amfiteatru Economic Journal, 2020)
Crowdlending is a disruptive financial tool that has been increasingly requested by SME 's to cover their capital needs. However, the growth of this technological development is being limited by the existing risk of default resulting in loss for lenders. To deal with this, funding platforms have started to offer more sustainable products such as the guaranteed loans. These special loans are backed by a Mutual Fund so Lenders minimise the risk of suffering the consequences of a default. This study aims to investigate the importance of factors related to loan characteristics, investor type and borrower's characteristics, in the crowdlending campaign success. To perform the analysis, we use Partial Least Squares (PLS) technique over a sample of 196 guaranteed loans from the pioneer platform in Spain offering that type of loans (MytripleA). Results indicate that the characteristics with greater influence in guaranteed crowdlending success are those related to the investors and the loans, while SME's factors seem not to have any impact. We consider that our results are interesting for both the funding platforms and the SME's seeking for funds.
Keywords: G23; G41; O33; Q55; 330; disruptive technologies; SME's; crowdlending; Peer-to-Business (P2B); guaranteed loans; success factors; Partial Least Squares (PLS)